Modifikasi Mesin Pencacah Rumput Gajah Menghasilkan Bahan Baku Kompos - Sianturi, Tulus Lamganda; Saparin, Saparin; Rodiawan, Rodiawan; Setiawan, Yudi; Sari Wijianti, Eka (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
The increase in the area of agricultural land in Indonesia makes the need for fertilisers continue to increase. Compost is one type of natural organic that is widely known by farmers that comes from organic materials that undergo weathering processes due to interactions between microorganisms (decaying bacteria) that work in it. Elephant grass is one of the plants that can be used as compost and has enormous potential. The existing elephant grass chopping machine still uses a serrated blade. So that the chopping cannot be chopped properly. In this study, the elephant grass chopping machine will be modified into an elephant grass chopping machine that uses HSS (High Speed Steel) material blades and the machine is driven by a 1 hp electric motor. The purpose of this research is to change the elephant grass chopping machine with HSS (High Speed Steel) blades and to make cutting faster. The research method used is experimental research using the French method and the Reverse Enginering Method The design process of the elephant grass chopping machine uses the Solidwork application. The test material used is 1000gr for one test. The resulting average is perfectly chopped as much as 897 gr, not perfectly chopped as much as 17.7 gr left / in the tube 84 gr, with a time of 60.08 seconds. The production capacity of the machine is 56.06 kg/hour. The machine that has been made is able to chop elephant grass with product efficiency.